Influence of Financial Risk to The Profitability of Sharia Banking In Indonesia - Pani Akhiruddin Siregar; Amiur Nuruddin; M. Yusuf (Management Department Universitas Islam Negeri Sumatera Utara, 2019)
This research aims to deeply analyze the impact of CAR risk, NPF risk, BOPO risk, FDR risk and ROE risk to profitability. The profitability indicator is ROA variable. Quantitative data types in the form of monthly time-series data From The Financial Ratio Report of Sharia Commercial Bank and Sharia Business Unit published by Sharia Banking Directorate, Bank Indonesia and the Bank Licensing and Banking Information Department, Indonesia Financial Services Authority through Sharia Banking Statistics Bank Indonesia/Indonesia Financial Services Authority from January 2006 to January 2018. The results showed: (1) A regression model on the independent variable simultaneously affects the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (2) The CAR variable and FDR variable influential positive and significant toward ROA variable; NPF variable influential negative and significant toward ROA variable; BOPO variable influential negative and insignificant toward ROA variable; ROE variable influential positive and insignificant toward ROA variable.Keywords: financial risk, profitability, Sharia banking